Narrative review on role of vitamin D in type II diabetes and hyperlipidemia - Elbarghathi, N. M.; S. Ahwaide, Hoda; F. Mohamed, Fatma (Libyan Journal of Science &Technology, 2022)
t is widely known that type II diabetes and hypo-vitaminosis D are very prevalent health problems worldwide. Vitamin D deficiency has emerged as an important risk factor in the pathogenesis and prevention of type II diabetes and hyperlipidemia. The key goal of this narrative review, through performing literature survey, is to consolidate results of relevant studies and consequently help direct future research in this area. Furthermore, highlighting the influence of vitamin D supplementation on beta-cell function, glycemic control; insulin sensitivity and lipid profile are other key aims of this review. For that end, several observational and interventional studies, conducted during the period (2003–2017) on animals and humans, have been reviewed. The key findings of this review are the significant inverse associations between serum 25(OH)D3 level and insulin resistance, glycemic index, type II diabetes and lipid parameter has been noticed in the majority of such observational studies in human. In addition, both in vivo and in vitro animal studies have proved the significant role of vitamin D in regulating beta-cell function, insulin sensitivity, and cholesterol biosynthesis, while interventional studies revealed contradicting results. The short-term interventional studies reported improvement in fasting blood sugar (FBS), insulin secretion and insulin resistance in vitamin D deficient-type II diabetic patients. On the other hand, the long-term interventional studies did not produce consistent results. Hence, the key value of this work is to provide guidance to researchers and health professionals on such specific subject. Finally, the review concludes with research limitations and puts forward future recommendations.